2006
DOI: 10.1002/mnfr.200600037
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of lutein production by heterotrophic Chlorella at various pH and temperatures

Abstract: Kinetics of lutein production by heterotrophic Chlorella protothecoides was investigated with respect to pH and temperature. Flask cultures with initial pH 5.0-8.0 were carried out, and it was found that pH 6.0 was optimal for the algal growth. Further tests in fermentors showed that the highest biomass concentration, maximum cellular lutein content and lutein yield were achieved at pH 6. 6. In addition, it was shown that optimal biomass concentration and lutein yield were obtained at 28 degrees C, while appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…However the heterotrophic growth was seriously inhibited when the initial pH value was too high to 10.0 or too low to 4.0 (p < 0.05). Results from Shi et al (2006), Jiang and Chen (2000) also suggested that the pH values of 6.0 and 7.2, a closely neutral condition of medium, were optimal for heterotrophic culture of C. protothecoides and C. cohnii respectively in order to obtain the highest biomass. A slight rise of lipid content when initial pH of medium was increased from 7.9 to 10.0 is reasonably contributed to the alkaline stress.…”
Section: Effect Of Ph and Temperature Influence On T Minus Heterotrophymentioning
confidence: 91%
“…However the heterotrophic growth was seriously inhibited when the initial pH value was too high to 10.0 or too low to 4.0 (p < 0.05). Results from Shi et al (2006), Jiang and Chen (2000) also suggested that the pH values of 6.0 and 7.2, a closely neutral condition of medium, were optimal for heterotrophic culture of C. protothecoides and C. cohnii respectively in order to obtain the highest biomass. A slight rise of lipid content when initial pH of medium was increased from 7.9 to 10.0 is reasonably contributed to the alkaline stress.…”
Section: Effect Of Ph and Temperature Influence On T Minus Heterotrophymentioning
confidence: 91%
“…Crypthecodinium cohnii can directly activate acetate to acetyl-CoA, the basic building block of fatty acids synthesis [48]. Also, it has been remarked that the heterotrophic growth of C. protothecoides supplied with acetate, glucose, or other organic compounds as carbon source results in high biomass and high content of lipid in cells [52]. To improve acetate or any other carbon source utilization, actively dividing microalgal cells from the exponential phase should be used as inoculums [2,41].…”
Section: Effect Of Acetate As Carbon Source With Ph Adjustmentmentioning
confidence: 99%
“…Recently, significant attention has been drawn to several alternative techniques for mass cultivation of algae, including heterotrophic and mixotrophic processes (Chen and Zhang 1997). Much work has been done on heterotrophic and mixotrophic growth of the green algae Chlorella (Shi et al , 2006Xu et al 2006) and Haematococcus (Kang et al 2005;Kaewpintong et al 2007). These algae can use different organic carbon sources such as glucose and acetate.…”
Section: Introductionmentioning
confidence: 99%